Bibliometric Analysis of Innovation and Economic Impact in Trends of Solar Energy Utilization in Agriculture - Judijanto, Loso; Arini, Rani Eka; Nugroho, Rahmat Joko (Westscience Press, 2024)
This paper presents a comprehensive analysis of thematic clusters, research trends, potential research opportunities, and author collaborations within the field of renewable energy and its impact on economic growth, using bibliometric visualizations generated by VOSviewer. We identified distinct thematic areas including renewable technologies such as solar and wind energy, and broader themes like energy utilization and economic implications. Our trend analysis revealed a significant temporal shift from technology-centric studies to a broader examination of how renewable energy integrates with economic systems and impacts global economic policies. Further exploration of less explored areas suggested potential research opportunities in the direct economic impacts of renewable energy, its role in industrial processes, and sustainable tourism. The examination of author collaboration networks illuminated the collaborative structures within the academic community, highlighting the formation of research clusters based on shared interests and common research goals. These findings underscore the evolving nature of renewable energy research, revealing both current focuses and prospective areas for future investigation.